Pelatihan Manajemen Laktasi pada Kader Posyandu Wilayah Kerja Puskesmas Tanjung Medang Rupat Utara - Ismawati Ismawati; Ilhami Romus (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Exclusive breastfeeding is one of the government programs to improve the nutritional status of toddlers aged 6-24 months. The World Health Organization (WHO) states that breast milk is the best source of nutrition for infants and toddlers or babies. Posyandu is a community-based health effort that is from, by, and for the community. Cadres are one of the elements that have an important role in health services such as monitoring the growth of children, toddlers and conducting counseling and providing information about maternal and child health. This is what drives this service activity which aims to increase the knowledge and skills of posyandu cadres in conducting breastfeeding counseling. This activity was carried out in the work area of the Tanjung Medang Health Center, Rupat Utara District, Bengkalis Regency from July to November 2022. The training was carried out using lecture, discussion, and question and answer methods using laptop media, projectors, and module books. This service activity was attended by 25 posyandu cadres. Most of the training participants were in the age range of 20-35 years (52%) and most of them had high school education (52%), the rest had elementary school education (24%), university (16%) ) and junior high school (8%). The results of the evaluation showed an increase in cadres' knowledge regarding lactation management. It is hoped that these cadres will then pass on their knowledge and skills to the families/mothers around them so that they can increase exclusive breastfeeding outcomes.